Share

Books Shortlist

# If the Roots of the Equations ( a 2 + B 2 ) X 2 − 2 B ( a + C ) X + ( B 2 + C 2 ) = 0 Are Equal, Then - CBSE Class 10 - Mathematics

ConceptSolutions of Quadratic Equations by Factorization

#### Question

If the roots of the equations $\left( a^2 + b^2 \right) x^2 - 2b\left( a + c \right)x + \left( b^2 + c^2 \right) = 0$ are equal, then

• 2b = a + c

• b2 = ac

• $b = \frac{2ac}{a + c}$

• b = ac

#### Solution

The given quadric equation is  $\left( a^2 + b^2 \right) x^2 - 2b\left( a + c \right)x + \left( b^2 + c^2 \right) = 0$, and roots are equal.

Here,  a = (a^2 +b^2), b = -2b(a+c) and, c = b^2 +c^2

As we know that D = b^2 - 4ac

Putting the value of  a = (a^2 +b^2), b = -2b (a + c) and, c = b^2 + c^2

= {-2b (a+c)}^2 - 4 xx (a^2 + b^2) xx (b^2 + c^2)

= 4a^2b^2 + 4b^2 c^2 + 8ab^2c - 4(a^2 b^2 + a^2 c^2 + b^4 + b^2 c^2)

=4a^2b^2 + 4b^2c^2 + 8ab^2c - 4a^2 b^2 - 4a^2c^2 - 4b^4 - 4b^2c^2

= +8ab^2c -4a^2c^2 - 4b^4

-4(a^2c^2 +b^4 - 2ab^2c)

The given equation will have equal roots, if D =0

-4(a^2c^2 +b^4 - 2ab^2c) = 0

a^2c^2 +b^4 - 2ab^2 c = 0

(ac - b^2)^2 = 0

ac  -b^2 = 0

ac = b^2

Is there an error in this question or solution?

#### APPEARS IN

Solution If the Roots of the Equations ( a 2 + B 2 ) X 2 − 2 B ( a + C ) X + ( B 2 + C 2 ) = 0 Are Equal, Then Concept: Solutions of Quadratic Equations by Factorization.
S